Pathophysiology and Treatment of Major Depressive Disorder: The Role of Nuclear Receptors Modulate Inflammasomes - Wang, Han; Kan, Wei-Jing; Feng, Yuan; Feng, Lei; Yang, Yang; Chen, Pei; Xu, Jing-Jie; Si, Tian-Mei; Zhang, Ling; Wang, Gang; Du, Jing (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
This review summarizes the evidence on nuclear receptors (NRs), such as glucocorticoid receptor, mineralocorticoid receptor, estrogen receptor, aryl hydrocarbon receptor, and peroxisome proliferator-activated receptor, in modulating the inflammasome activity and depression-associated behaviors. Major depressive disorder (MDD) is highly prevalent and is a significant cause of mortality and morbidity worldwide. Currently, conventional pharmacological treatments for MDD produce temporary remission in < 50% of patients; therefore, there is an urgent need for a wider spectrum of novel antidepressants to target newly discovered underlying disease mechanisms. Another important hypothesis of depression, several lines of evidence have established an association between MDD and the neuroimmune pathway, although some psychiatrists have argued about the causal relationship between inflammation and depression. Accumulated evidence has shown that immune inflammation, particularly inflammasome activity, plays an important role in the pathophysiology of MDD. This review provides evidence from an endocrine perspective to understand the role of activated NRs in the pathophysiology of MDD and to provide insight into the discovery of antidepressants with novel mechanisms for this devastating disorder. Cumulative studies have shown that activation of the NRs may directly change the activity of inflammasomes to modulate the levels of mature forms of caspase-1 and IL-1\(β\). Caspase-1-mediated programmed cell death and surface stability of the AMPA receptor in the hippocampus, are essential for depression-like behavior.